Facile Fabrication of Single-Layer Janus Membrane for Underwater Bubble Unidirectional Transport - Liu, Chunhua; Peng, Yun; Huang, Conglin; Shang, Jiaoping; Liu, Guohua; Li, Yibao (Frontiers in Physics, 2022)
Janus membranes with superwetting play an important role in many fields, such as oil/water separation, unidirectional fluid transportation, microfluidic devices, intelligent ion valve, mass/heat transfer applications, etc. Although there has been some progress in the preparation of the Janus membranes with unidirectional penetration, it still remains a great difficulty for facile fabrication of two dimensional Janus membranes with a large pore structure and stable bubble unidirectional transport in the water. Herein, a signal-layer Janus membrane with superwetting is fabricated via the method of liquid-regulated hydrophobic modification strategy. The resultant Janus mesh achieves underwater unidirectional penetration. Namely, Underwater bubbles can pass unidirectionally from superhydrophobic side to hydrophilic side, but are blocked from passing through in the opposite direction. Thus, this Janus membrane with the unidirectional underwater bubbles penetration “diode” performance. We believe this work can promote the development of multi-dimensional Janus materials for fluid directional transport.